Enhanced Electrocatalysis for Energy‐Efficient Hydrogen Production over CoP Catalyst with Nonelectroactive Zn as a Promoter. Issue 15 (27th April 2017) - Liu, Tingting; Liu, Danni; Qu, Fengli; Wang, Dengxing; Zhang, Ling; Ge, Ruixiang; Hao, Shuai; Ma, Yongjun; Du, Gu; Asiri, Abdullah M.; Chen, Liang; Sun, Xuping
Abstract : As a non‐toxic species, Zn fulfills a multitude of biological roles, but its promoting effect on electrocatalysis has been rarely explored. Herein, the theoretic predications and experimental investigations that nonelectroactive Zn behaves as an effective promoter for CoP‐catalyzed hydrogen evolution reaction (HER) in both acidic and alkaline media is reported. Density function theory calculations reveal that Zn doing leads to more thermal‐neutral hydrogen adsorption free energy and thus enhanced HER activity for CoP catalyst. Electrochemical tests show that a Zn0.08 Co0.92 P nanowall array on titanium mesh (Zn0.08 Co0.92 P/TM) needs overpotentials of only 39 and 67 mV to drive a geometrical catalytic current of 10 mA cm ‐2 in 0.5m H2 SO4 and 1.0m KOH, respectively. This Zn0.08 Co0.92 P/TM is also superior in activity over CoP/TM for urea oxidation reaction (UOR), driving 115 mA cm ‐2 at 0.6 V in 1.0m KOH with 0.5m urea. The high HER and UOR activity of this bifunctional electrode enables a Zn0.08 Co0.92 P/TM‐based two‐electrode electrolyzer for energy‐saving hydrogen production, offering 10 mA cm ‐2 at a low voltage of 1.38 V with strong long‐term electrochemical stability. Abstract : Zn functions as an effective promoter for CoP‐catalyzed hydrogen evolution reaction in both acidic and alkaline media. Its high activity toward urea oxidation reaction enables Zn0.08 Co0.92 P/titanium mesh as a durable bifunctional catalyst electrode for energy‐efficient hydrogen production with a voltage of 1.38 V to drive 10 mA cm −2 in 1.0m KOH in the presence of 0.5m urea.